Situation of the offer Doctorate in Education Programs in Chile - Ganga-Contreras, Francisco; Rodriguez-Ponce, Emilio; Castillo, Juan; Viancos-González, Patricio (Revista de Ciencias Sociales, 2023)
The quality training demand has increased due to the complexity of modern society. As education is the fundamental foundation for people’s progress, this research is interested in analyzing the offer of doctoral programs in education in Chile ( quality and quantity), aiming to generate information for the decision-making process of the various interest groups. This research was a descriptive study involving primary and secondary sources of information (scientific articles, enrollment database, and web pages); a relevant source is the Higher Education Information System of the Chilean Ministry of Education, whose version is updated until July 2022. A growth of 2,680.5% was detected in the enrollment of postgraduate students in Chile between 1984 and 2022, which exceeds the higher education system, which has multiplied its enrollment by 6.8 times in the same period, which in the specific case of doctorates is 46 times. The relevance of accreditation systems underscores the need for a more substantial commitment to ensure quality education at all levels, especially in doctoral programs in this area.